Nanoscale graphene nanoparticles conductive ink mechanical performance based on nanoindentation analysis - Salim, Mohd Azli; Saad, Hartini; Masripan, Nor Azmmi; Md. Saad, Adzni; Dai, Feng (Universiti Malaysia Perlis, 2020)
Common conductive inks can be classified into three categories, which are noble metals, conductive polymers and carbon nanomaterials. Carbon nanomaterials offer many potential opportunities to be applied in printed and flexible electronics. Therefore, this paper aims to produce highly functional conductive ink using graphene nanoparticles with epoxy as a binder. As a baseline, graphene-filler conductive ink was formulated using a minimum percentage at the beginning. Then, the filler loading was increased based on the required conductivity level. This is to make sure the materials are in contact with each other and the movement of an electron will become easier. The formulation of ink, mixing process, printing process and curing process were performed to produce highly conductive graphene ink. The electrical and mechanical properties were assessed using a Four-point probe as per ASTM F390 and Dynamic Ultra Micro Hardness (DUMH) test as per ASTM E2546-1. Graphene Nanoplatelet (GNP) aggregates are unique nanoparticles consisting of shorts stacks of graphene sheets with platelets shape. They typically consist of aggregates of sub-micron platelets that have a particle diameter less than 2 microns, typical particle thickness of a few nanometers, a bulk density of 0.2 to 0.4 g/cc, an oxygen content of <2 wt%, the carbon content of >98 wt%, and in the form of black granules. In this paper, the effect on sheet resistivity and nanoindentation for straight line-shape, curve-shape, square-shape and zigzag-shape circuits printed on Thermoplastic Polyurethane (TPU) substrate using Graphene Nanoparticles (GNPs) conductive ink as the connection material were investigated. The samples in this study were fabricated using a screen-printing method with a fixed circuit width of 1 mm, 2 mm and 3 mm. The straight-shape circuit, curve-shape, square-shape and zig-zag-shape circuits represent the electrical connection with 180°, A°, 90° and B° directional angles. The effect of varying circuit width on the sheet resistivity of all printed circuit mentioned before was later measured using Four-point probe. Nanoindentation was conducted using instrumental machines with indenter load and indenter displacement that can be continuously and simultaneously recorded during indenter loading and unloading